CSR Feels Good, But Does It Work? From Affective Brand Image to Customer Loyalty - Potu, Tania Monica; Banda, Hope Wilfred; Siahaya, Janice Carysa (Business Innovation Management and Entrepreneurship Journal, 2026)
This study examines how Corporate Social Responsibility (CSR) influences customer satisfaction and customer loyalty through the mediating role of emotional brand image, addressing a short- and long-term perspectives in the fast-food industry. A hundred respondents from Jakarta who are familiar with CSR activities participated in a quantitative survey, and SPSS was used to analyze the results. The results show that CSR significantly improves emotional brand image (β = 0.668; sig = 0.000; Adj R² = 0.440), explaining 44% of the variation in brand image. However, consumer satisfaction is not substantially impacted by affective brand image (β = 0.127; sig = 0.111), indicating that short-term contentment cannot be driven only by emotional views. Conversely, consumer loyalty is strongly influenced by customer satisfaction (β = 0.477; sig = 0.000; Adj R² = 0.594), highlighting its importance for long-term outcomes. The study concludes that while CSR effectively builds emotional brand perceptions, companies must align these with actual service and product quality to achieve sustainable satisfaction and loyalty.